The giving effects of biscuits and tempeh-based flour cakes as supplemetary feeding towards improvements in body weight and height in children suffering malnutrition 2015 - Oktovina Rizky; Bambang Wirjatmadi; Merryana Adriani (Universitas Wijaya Kusuma Surabaya, 2015)
Background: Nutritional problem in children is considered as a major issue and one that should receive priority in treatment is concerning to malnutrition. Malnutrition in children occurs due to insufficiency in energy and protein. Energy and protein are required in supporting rapid growth in children.Objective: to learn the giving effects of biscuits and tempeh-based flour cakes as supplementary feeding towards improvements in body weight and height of children under five suffering malnutrition in one of Public Health Center working area, northern region of Kediri Municipality.Methods: This study used a Randomized Control Triall Design, towards groups of children under five by providing tempeh-based flour cakes for supplementary feeding in the treatment group and by providing biscuits for supplementary feeding in control group. Samples were as many as 30 children under five and the data were being analyzed using peason and pre-post differences analysis was done using paired samples T-testResult: There was significant difference between body weight and body height after provision of providing biscuits and tempeh-based flour cakes for supplementary feeding with p = 0.001 (p <α) for the treatment group and p = 0.001 (p <α) for the control group.Conclution: Providing and tempeh-based flour cakes in the treatment group for 30-days gave influence on increasing body weight and height.